The Effect of Self-Assessment Systems, Tax Audits, and Vat Refunds on Value Added Tax Revenues (Empirical Study At KPP Pratama Jakarta Palmerah from 2016 to 2020) - Dwi Wulandari; Juitania Juitania (President University, 2022)
Tax is the main source of state revenue. For this reason, taxes are a very important factor for state finances, especially to ensure the continuity of national development which is continuously carried out. Receipt of Value Added Tax is strongly influenced by the awareness of the Taxable Entrepreneur in depositing and reporting the Value Added Tax payable because the Taxable Entrepreneur is directly the bearer of the burden of payment and is responsible for depositing Value Added Tax to the state treasury, as well as claiming the return of Value Added Tax which is the right of the Taxable Entrepreneur. This study aims to determine the effect of the Self-Assessment System, Tax Audit and VAT Refunds on Value Added Tax Receipts at KPP Pratama Jakarta Palmerah from 2016 to 2020. The type of data used is secondary data in the form of a time series study for 5 years with monthly data units. The samples taken were the realization of Value Added Tax receipts, the number of Periodic VAT SPTs, the total value of SKPs and the amount of VAT refunds per month at KPP Pratama Jakarta Palmerah for the 2016-2020 period. This study employs traditional assumption tests such as the normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test. The multiple linear regression method with EViews 10 was used as the analytical method in this study. According to the study's findings, the Self-Assessment System, Tax Audit, and VAT Refunds all have an impact on Value Added Tax Receipts at KPP Pratama Jakarta Palmerah during the 2016-2020 fiscal year. Meanwhile, this suggests that the Self-Assessment System has no effect on Value Added Tax Receipts, Tax Audit has a negative effect on Value Added Tax Receipts, and VAT Refunds has no effect on Value Added Tax Receipts.